LANGUAGE TEACHING TECHNIQUES AND CONTEMPORARY LINGUISTIC ISSUES (Konferensiyalar | Conferences, 2024)
This article explores various language teaching methods and their effectiveness in addressing current linguistic challenges. It discusses the importance of incorporating technology, cultural awareness, and communicative competence in language teaching practices. Additionally, it analyzes the impact of globalization, multilingualism, and digital communication on language education. proposed as substitutes.